Comparison of Development of New and Old Wheat Varieties at High Temperature Conditioning - Bekir Atar (Turkish Journal of Agriculture: Food Science and Technology)
For about 10 thousand years, new varieties have emerged naturally or artificial in wheat. Factors for the development of new varieties are fertilization, machine use, changing taste preferences and adaptation to climate change and exc. In the study; Apogee variety, which is one of the most recently developed varieties, has low sensitivity to vernalization and photoperiod, and Einkorn and Emmer, which is one of the oldest known varieties, and Tosunbey variety, which has been developed in our country in recent years, were compared in terms of agronomic characteristics. The research was carried out at room temperature and field conditions with spring planting. At room temperature, Apogee variety reached harvest maturity in 87 days, Emmer variety’s in 140 days, Tosunbey variety’s in 116 days. Since Einkorn variety could not meet the need for vernalization, its development ceased at stem elongation stage. All varieties have completed their development by meeting the need for vernalization in field conditions. Apogee variety reached harvest maturity in 93 days, Einkorn variety in 118 days, Emmer variety in 108 days, Tosunbey variety in 115 days. In land conditions, Apogee varieties ripen later, while other varieties ripened earlier. Thousand grain weights were 24.3 g in Apogee variety, 17.3 g in Emmer variety, 26.7 g in Tosunbey variety at room temperature conditioning, 11.3 g in Apogee variety, 20.3 g in Einkorn variety, 24.7 g in Emmer variety and 26.0 g in Emmer variety at field conditioning. In field condition, thousand-grain weights of Apogee variety decreased seriously.